EFEKTIVITAS KOMUNIKASI AKUN INSTAGRAM @SEHATSURABAYAKU SEBAGAI MEDIA INFORMASI VAKSINASI COVID-19 MASYARAKAT KOTA SURABAYA - Aini, Yusni Nur; Sudaryanto, Edy (Sintesa, 2023)
The effectiveness of using Instagram as a medium of communication is an action to see the extent of effort in communicating through an Instagram in obtaining or producing an effect of achieving a predetermined goal. The study aims to determine how much the level of communication effectiveness of the Instagram account @sehatsurabayaku as an information medium for the Covid-19 vaccination of the people of the City of Surabaya by using the theory of Communication Effectiveness from Andre Hardjana which consists of 6 indicators, receiver or user, content,timing, media, format and source. Research sampling used the Random Sampling sample technique with a total of 100 respondents. The research data was obtained through the dissemination of questionnaires to Instagram followers @sehatsurabayaku. The data analysis used is descriptive quantitative using the SPSS Version 25 program. The results of the study obtained a percentage result of 86.87%, which is included in the very effective category. So that shows that the Instagram account @sehatsurabayaku become a very effective media as a medium for information on the Covid-19 vaccination of the people of the City of Surabaya.